A Habit-Based Learning Model to Develop Discipline and Religious Values from an Early Age - E. Ernawati; I. Ismail (Golden Ratio of Data in Summary, 2026)
This study aims to describe and analyze the application of a habit-based learning model to foster discipline and religious values in early childhood. The habit-based learning model is an approach that emphasizes the consistent and structured repetition of positive behaviors in daily activities within the school environment. This study employed a qualitative approach with descriptive study methods, conducted in an early childhood education institution. Data collection techniques included observation, interviews, and documentation. Data analysis utilized data reduction, data presentation, and conclusion drawing techniques. The results indicate that the routine implementation of habit-based learning, such as group prayer, greetings, queuing, maintaining cleanliness, and time discipline, is effective in fostering discipline and instilling religious values from an early age. Teachers' exemplary behavior, consistent rules, and support from the school and family environment are key contributing factors to the success of this model. Thus, the habit-based learning model has proven to be a relevant and effective strategy for building the foundation of character and spirituality in children from an early age.